2017
DOI: 10.1590/s0100-736x2017000700018
|View full text |Cite
|
Sign up to set email alerts
|

Ultrassonografia modo B e Doppler na avaliação renal de cães submetidos à tomografia computadorizada após administração intravenosa de diferentes meios de contraste iodado

Abstract: Contrast-induced nephropathy (CIN) is an acute disease, secondary to intravascular administration of iodinated contrast media (ICM). The most important mechanisms of this nephropathy are intrarenal prolonged vasoconstriction, medular hypoxia, and ischemia associated with renal tubular damage due to contrast cytotoxicity. Owing to the limited information available in veterinary literature regarding these mechanisms this study aims to compare the renal effects of intravenous administration of two nonionic ICM of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Contrast-enhanced ultrasound can reportedly show changes in renal flow six weeks before creatinine values are significantly increased for the species, allowing an early diagnosis of renal diseases and their treatment 9 . The importance and reliability of Doppler flowmetry in identifying early changes in renal flow, anticipating irreversible structural damage to the kidneys, has also been described 6 , 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-enhanced ultrasound can reportedly show changes in renal flow six weeks before creatinine values are significantly increased for the species, allowing an early diagnosis of renal diseases and their treatment 9 . The importance and reliability of Doppler flowmetry in identifying early changes in renal flow, anticipating irreversible structural damage to the kidneys, has also been described 6 , 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al (2013) described that CEUS can show changes in renal ow six weeks before creatinine values are signi cantly increased for the species, allowing an early diagnosis of renal diseases and their treatment. Similarly,Melo et al (2006) andMartín et al (2017) described the importance and reliability of Doppler owmetry in identifying early changes in renal ow, anticipating irreversible structural damage to the kidneys. As such, the authors consider that there was no change in renal perfusion resulting from the treatment, and that the development of proteinuria and CKD were due to factors inherent to the patients and not the treatment.DaSilva et al (2014) reported that hematologic changes are common in patients with mammary neoplasia, often with presence of anaemia.…”
mentioning
confidence: 99%